ENHANCED ORAL BIOAVAILABILITY OF TENOFOVIR FROM IONOTROPICALLY GELLED MICROBEADS - VENKATESH, DHANDAPANI NAGASAMY; RAO, PREETY; RAJESHKUMAR, RAMAN (International Journal of Applied Pharmaceutics, 2019)
Objective: The main objective of the present investigation was to develop microbeads of tenofovir. Tenofovir, a BCS class III drug has a poor bioavailability of 25%, and it is administered 300 mg once a day. By incorporating the drug into a microparticulate carrier, it is expected that the dissolution profile and the oral bioavailability may be increased. Methods: Reinforced gellan-chitosan and calcium chloride beads of tenofovir were prepared by ionotropic gelation method employing various different concentrations of gellan, chitosan, calcium chloride and tenofovir. The beads were evaluated for various physico-chemical parameters such as particle size determination, drug entrapment efficiency, swelling studies, infra red spectroscopy study, differential scanning calorimetry, x-ray diffraction analysis, scanning electron microscopy, in vitro drug release study, cytotoxicity study and in vivo oral bioavailability studies. Results: From the results, it can be concluded that the formulation TB-III exhibited higher drug entrapment efficiency (46.09±0.21), a higher swelling index, sustained drug release for a period of 24 h. The pharmacokinetic profile of the drug from microbeads exhibited an increased oral bioavailability (1.25 times higher than that of pure drug), decreased elimination rate (1.32 times lesser for drug in microbeads) with prolonged elimination half-life (1.32 times higher than pure tenofovir). Conclusion: Tenofovir loaded microbeads demonstrated as a better delivery system for the modified release of drug and also to navigate the drawbacks associated with the conventional therapy.